Socioeconomic and environmental factors jointly shape beta diversity of woody species in eastern China. Issue 1 (24th March 2022) - Liu, Jinliang; Jiang, Bo; Yuan, Weigao; Jin, Chao; Jiao, Jiejie; Wang, Zhigao; Zhu, Jinru; Zhan, Xiaohao; Liu, Jiajia; Wu, Chuping
Abstract: Questions: Increasingly, studies have demonstrated that not only environmental factors but also socioeconomic factors are important in determining species richness patterns. However, few studies have explored their effects on beta diversity. Here, we aimed to answer two questions based on woody species composition in a number of geographical administrative divisions: (1) how does beta diversity change with socioeconomic and environmental factors; and (2) what is the relative importance of socioeconomic and environmental factors in driving beta diversity of woody species? Location: Eastern China. Methods: We used abundance‐based beta diversity (Bray–Curtis) and species accumulation rate to quantify beta diversity of woody species of 20 counties in eastern China. Linear regression models were used to test the relationships between beta diversity and socioeconomic and environmental factors. The relative importance of socioeconomic and environmental factors in driving beta diversity was investigated using the variation partitioning method. Results: We found that elevation, annual precipitation, and location significantly affected species composition. Species accumulation rate increased significantly with Gross Domestic Product (GDP), GDP per capita and human population density, and decreased with forest cover, topographic and climatic heterogeneity. In addition, abundance‐based beta diversity increased significantly with human population density. Moreover, socioeconomic factors, topographic and climatic heterogeneity independently explained 25%, 15%, and 1% of abundance‐based beta diversity separately. Conclusion: Socioeconomic factors may have significant effects on beta diversity patterns of woody plants. Our study highlights the urgent need to consider socioeconomic factors when exploring large‐scale biodiversity patterns in human‐dominated landscapes and formulating related forest management strategies. Abstract : We analyzed effects of socioeconomic and natural environmental factors on beta diversity of forests located in 20 counties in eastern China. Elevation, annual precipitation, and county where forest was located significantly affected species composition. Beta diversity increased significantly with GDP and population density. Socioeconomic factors explained more variance in beta diversity patterns than environmental factors.